Efficacy of a locally produced microbial phytase from Enterobacter sakazakii ASUIA273 on body weight and hemato-biochemical constituents in broiler chickens - Islam, R.; Ideris, Aini; Kasim, Azhar; Omar, Abdul Rahman; Meor Hussin, Anis Shobirin; Farhana Yasmin, (Veterinary Association Malaysia, 2011)
An experiment was carried out in broiler chicks fed different doses of locally produced microbial phytase supplementation to observe their growth performance as health status, and to investigate the changes of hematological and biochemical values. A total of 144 chicks (Cobb) at one-day old were allocated to 4 treatment (T) groups with 12 cages comprising 3 replicates, each cage containing to 12 birds. Experimental formulating diets arranged with 4 levels of 0, 500, 1000 and 1500 phytase enzyme unit (FTU/kg-I) as considered as Th T2, T3, T4 respectively. They were maintained formulating diet on these dietary treatments from 1 to 42 d of age with feed and water made available for ad libitum consumption. At 1 week interval 2 birds from each treatment were weight through out experimental period for assessing the growth performance. For determining the changes of hematological (RBC, Hb, PCV, MCV, MCHC, WBC, Heterophil, Eosinophil, Basophil, Lymphocyte, Monocyte, Thrombocyte and Icterus Index) and biochemical (Albumin, Total Protein, ALT, ALP, AST, GGT, LDH, Cholesterol, Triglyceride, Glucose, Ca, P, Na, K, Cl, Urea, Creatine and Uric acid) values at the age of 6 weeks randomly selected 2 birds were slaughtered and blood were collected. Data were subjected to analysis of variance (ANOVA) using the least significant difference (LSD) by PC-SAS software (SAS Institute, 2009). Data showed that body weight was not affected at periods of 1si and 2nd weeks of age among different treatment groups. But, at ages from 3rd to 6th weeks, weight gains at four treatment gIZ.Qupwsere increased almost sequentially and consistantly, and had been showed more different and significant (p:s 0.05) increased at 4th and 5th weeks of age from the control. No significant and constant treatments effects were observed on blood and biochemical parameters except eosinophil: Accordingly, it can be recommended to use an uncentrifuged microbial phytase in broiler diet during the period from 4th - 5th weeks of age, to achieve increased weight gain without changing hemato-biochemical parameters.